EDUKASI PENTINGNYA PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DENGAN CUCI TANGAN 6 LANGKAH DI RUANG RAWAT INAP MARWA RSI ARAFAH JAMBI - yusnilawati yusni; Indah Mawarti; Syafira Nurliza Mahendra; Rts Netisa Martawinarti; Putri Irwanti Sari; Rina Oktaria (Jurnal Pengabdian Masyarakat, 2025)
Background: One important aspect of PHBS is handwashing with soap, which has been proven to be an effective way to prevent various infectious diseases. In the healthcare sector, handwashing with soap is very crucial, especially in preventing nosocomial infections, namely infections that occur in hospitals due to the transmission of bacteria and viruses from the non-sterile hospital environment. Medical personnel and patients' families play a major role in preventing these infections. However, many patients' families still do not pay attention to hand hygiene when visiting patient treatment rooms. Objective: This community service activity aims to increase the understanding of patient families regarding the importance of hand hygiene both before and after carrying out activities while the patient and family are in the treatment room at the hospital. Objective: This community service activity aims to increase the understanding of patient families regarding the importance of hand hygiene both before and after carrying out activities while the patient and family are in the treatment room at the hospital. Method: Education was carried out through lectures and direct demonstrations in the Marwa Inpatient Room, RSI Arafah Jambi with the participation of 15 people, using leaflets and flipcharts. Results: The results of the activity showed an increase in participants' understanding of the six steps of handwashing according to WHO standards and an increase in the understanding of patient families regarding risk factors for falls in patients. Before the education, only 6 out of 15 participants (17.14%) understood the material. After the education, all participants (100%) showed a good understanding. Thus, there was an increase in understanding of 82.86%. Participants also actively discussed and showed high enthusiasm in the activity. With this education, it is hoped that hand hygiene practices using 6 steps can be applied consistently in daily life, so that clean and healthy living behavior (PHBS) by washing hands through 6 steps can be continuously implemented. Keywords: Clean and Healthy Living Behavior (PHBS), 6-Step Hand Washing